A Peningkatan Hasil Belajar Pendidikan Pancasila Menggunakan Model Learning Cycle di Kelas V SDN 03 Pakan Labuah Kota Bukittinggi: Peningkatan Hasil Belajar Pendidikan Pancasila Menggunakan Model Learning Cycle - Naftalika, Prilly; Anita, Yesi; Iraqi, Hana Shilfia; Waldi, Atri (Global Action and Education for Society, 2025)
This research is motivated by the low learning outcomes of students, this is because teachers have not used innovative learning models that can attract the attention of students. The purpose of this study was to describe the improvement of Pancasila Education learning outcomes using the Learning Cycle model in Class V SDN 03 Pakan Labuah Bukittinggi City. This research is a classroom action research (PTK) that uses qualitative and quantitative approaches. This research was carried out in two cycles, namely cycle I consisting of 2 meetings and cycle II consisting of 1 meeting. Each cycle includes four stages, namely planning, implementation, observation, and reflection. The subjects of this research were teachers and students of class V SDN 03 Pakan Labuah Bukittinggi City with 22 students, 10 female students and 12 male students. Data collection techniques in the form of tests and non-tests. The results of this study are guided by the recapitulation table of the research results of cycle I and cycle II which have been presented in the discussion section, the results of this study show: First, the teaching module of cycle I with an average of 85.41 (B) and increased in cycle II to 95.85% (SB). Second, the results of the implementation of learning aspects of teachers in cycle I with an average of 81.94 (B) and increased in cycle II to 94.44% (SB). Third, the results of the implementation of learning aspects of students in cycle I with an average of 81.94% (B), and increased in cycle II to 94.44% (SB). Fourth, the learning outcomes of cycle I students with an average of 78.17 (C) and increased in cycle II to 90 (SB). Based on these results, it can be concluded that the use of the Learning Cycle model can improve the learning outcomes of Pancasila Education class V SDN 03 Pakan Labuah Bukittinggi City.